Effect of Dangke consumption on body weight, blood glucose, and total cholesterol in rats subjected to high-fat and fructose diet - Ahmad; Kadir, Syahrijuita; Malaka, Ratmawati; Ilhamuddin; Soraya, Gita Vita; Hardjo, Marhaen (Gaceta Médica de Caracas, 2023)
Obesity occurs due to an imbalance in caloric intake, leading to excess fat accumulation in adipose tissue. This condition is associated with hyperglycemia and abnormal lipid levels. Dangke, a traditional Indonesian cheese, contains lactic acid bacteria and bioactive peptides known for their health benefits. This study aims to assess the effects of dangke consumption on body weight, glucose, and total cholesterol levels in rats subjected to a high-fat and fructose diet (HFFD). This research employed an experimental laboratory design. Twenty-four Sprague-Dawley rats, with weights ranging from 100 to 200 g, were divided into six groups, each consisting of four rats. Group 1 (ND) (received a normal diet. Group 2 (HFFD) was provided with a high-fat and fructose diet).